Pelanggaran Kesantunan dalam Acara Comedy Night Live di Net TV: Kajian Pragmatik - Swadiari, I Gusti Ayu Ketut; Simpen, I Wayan (Humanis; Vol 20 No 1 (2017), 2017)
This research entitled “The Violations of Politeness in Comedy Night Live on NET. TV: A Pragmatic Study. There are two problems analyzed in this research, namely violation of the principle of politeness and the violation factors contained in CNL on NET. TV. The aims of this research are to know the violation of the principle of politeness and the factors that caused violation. The theories used are principles of pragmatics stated by Leech and the Ethnography of Communication by Hymes. Several techniques and methods were applied to achieve the aims of this study. The data source used as the analysis material is the CNL video on Net TV. This study covers all CNL videos on Net TV in July-December 2015 every Saturday and Sunday. In this research, the principle of pragmatics and the theory of situation context is used. Based on the analysis that has been done on CNL on NET. TV, it can be concluded as follows. First, the violation of the principle of politeness is most often done against the maxim of praise in the CNL show on NET. TV. Second, the violation factor is influenced by the age factor that proves that comedy shows are not concerned about respect.